2006
DOI: 10.1002/art.22085
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin reduces disease activity and normalizes T cell activation–induced calcium fluxing in patients with systemic lupus erythematosus

Abstract: Objective. Systemic lupus erythematosus (SLE) is an autoimmune disease of unknown origin. Current treatment options are often ineffective or poorly tolerated. Recent observations have revealed mitochondrial hyperpolarization and enhanced Ca 2؉ fluxing in T cells from SLE patients. Rapamycin, a lipophilic macrolide antibiotic that regulates mitochondrial transmembrane potential and Ca 2؉ fluxing, has been used safely and effectively to treat renal transplant rejection since 1999. In addition, rapamycin has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
256
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 299 publications
(267 citation statements)
references
References 22 publications
8
256
0
3
Order By: Relevance
“…RAPA significantly reduced or prevented many pathologic features of lupus normally seen in the MRL/lpr mouse [67]. RAPA treatment of patients with SLE normalized cytosolic and mitochondrial Ca 2+ levels and T cell activation-induced rapid Ca 2+ fluxing, without influencing MHP [68], indicating that increased Ca 2+ fluxing is downstream or independent of MHP in the pathogenesis of T-cell dysfunction in SLE. Interestingly, the mammalian target of rapamycin (mTOR) may be activated by enhanced production of NO [69].…”
Section: Mitochondrial Hyperpolarization and Increased No Production mentioning
confidence: 91%
“…RAPA significantly reduced or prevented many pathologic features of lupus normally seen in the MRL/lpr mouse [67]. RAPA treatment of patients with SLE normalized cytosolic and mitochondrial Ca 2+ levels and T cell activation-induced rapid Ca 2+ fluxing, without influencing MHP [68], indicating that increased Ca 2+ fluxing is downstream or independent of MHP in the pathogenesis of T-cell dysfunction in SLE. Interestingly, the mammalian target of rapamycin (mTOR) may be activated by enhanced production of NO [69].…”
Section: Mitochondrial Hyperpolarization and Increased No Production mentioning
confidence: 91%
“…A small study of SLE patients treated with rapamycin showed improvement in disease activity and steroid dose reduction (22). Another pathway for activation of mTOR in lupus T cells is from depletion of glutathione, which regulates the elevation of mitochondrial transmembrane potential or mitochondrial hyperpolarization (23).…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin in theory would suppress geroconversion downstream of progerin. Furthermore, rapamycin prevents atherosclerosis in animal models of accelerated atherosclerosis and accelerated atherosclerosis is one of the main symptoms of progeria leading to death [73].…”
Section: Progeria (Hutchinson-gilford Progeria Syndrome (Hgps))mentioning
confidence: 99%